Peningkatan Minat Belajar Matematika Dengan Menerapkan Model Pembelajaran Kooperatif Tipe Problem Based Learning (PBL) Pada Materi Matriks - Wanda Eka Pratiwi; Suhartono Suhartono (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to increase interest in learning and critical thinking of class The background to this research is because students' low interest in learning, especially in learning mathematics. In the learning process, a student's interest in learning plays an important role in the teaching and learning process, because if students have low interest in learning, it will be difficult for them to receive knowledge from the teacher, so that learning outcomes will be less effective. This research uses the Classroom Action research method (PTK) which consists of two cycles. The techniques used for data collection are: planning, implementing actions, observing and evaluating and reflecting. Before that, initial observations were carried out in order to find out information or characteristics of students. The results of the research show that the PBL type cooperative learning model was applied to matrix material for class XI students at SMA Negeri 21 Surabaya. This can be seen from the increase in implementation results, observation and reflection. Students' learning activities experienced a significant increase in cycle two compared to cycle one. By learning using the PBL method, it is possible for students to more easily understand the material because it relates to problems around them and with discussions students can work together and help each other if they experience problems. Apart from that, this method can also help develop their critical thinking and communication skills.